HUBUNGAN KONDISI GEOLOGI TERHADAP ALTERASI DAN MINERALISASI ENDAPAN EPITHERMAL DAERAH SUALAN, KECAMATAN TALEGONG, KABUPATEN GARUT, PROVINSI JAWA BARAT - Paramitha Eka Kumala Sari (Geological Engineering E-Journal, 2013)
In exploration process of epithermal deposit, it is important to understand alteration and mineralization. The presence of alteration  and  mineralization zones help development of ore mineral exploration. Hydrothermal alteration is change of the chemistry, physics, mineralogy and origin textures of rocks as it interacts with the hydrothermal fluid. Alteration and mineralization  zones has characteristics and certain minerals in each area.The research purposes are to determine the geological conditions include morphology, lithology and geological structure, to know the type of alteration, and to know the characteristics of epithermal deposit in the research area. The research method consist of survey method and analysis method. Survey method was done by surface mapping. Analysis method include petrological analysis, petrographic analysis, mineragraphy analysis, ASD analysis (Analytical Spectral Devices) and geological structure analysis.Geomorphology of Sualan  area is divided into two landforms are very steep volcanic mountains and rugged hilly volcanic landforms. Lithology consists of tuff breccia, andesite lava, banded tuff, intrusion of hornblende andesite, andesitic breccia and tuff. The geological structure is contained systematic joint that is have  strike/dip N142°E/79° dan N257°E/81° in Cibaliung River, N291°E/64° dan N153°E/65° in Cibaliung Beet River and N337°E/53° dan N87°E/49° in Citutugan River and fault structures are left slip fault Cibaliung with pitch 3° and shear zone N 170°E/76°, right reverse slip fault Cibaliun Beet with pitch 70° and shear zone N 300°E/76°, reverse left slip fault Citutugan with pitch 33° and shear zone N 350°E/48°. This structure are formed  at last Pliocene with main emphasis northwest-southeast. Alteration zones consists of  chlorite-smectite ±illite alteration zone, propylitic alteration; kaolin-illite alteration zone, argillic alteration and quartz -kaolin-alunite±dickite  alteration zone, advanced argillic alteration. Mineralization consist of disseminated pyrite and gold (Au) as ore minerals and oxide minerals  such as jarosite, hematite and goetite that change acid mineral. It can indicate that it is included high sulphidation epithermal deposit .